Mucosal Therapy of Multi-Drug Resistant Tuberculosis With IgA and Interferon-γ - Tran, Andy C.; Diogo, Gil R.; Paul, Matthew J.; Copland, Alastair; Hart, Peter; Mehta, Nickita; Irvine, Edward. B.; Mussá, Tufária; Drake, Pascal M. W.; Ivanyi, Juraj; Alter, Galit; Reljic, Rajko (Frontiers in Immunology, 2020)
New evidence has been emerging that antibodies can be protective in various experimental models of tuberculosis. Here, we report on protection against multidrug-resistant Mycobacterium tuberculosis (MDR-TB) infection, using a combination of the human monoclonal IgA 2E9 antibody against the alpha-crystallin (Acr, HspX) antigen and mouse interferon-gamma in mice transgenic for the human IgA receptor, CD89. The effect of the combined mucosal IgA and IFN- treatment was strongest (50-fold reduction) when therapy was applied at the time of infection, but a statistically significant reduction of lung bacterial load was observed even when the therapy was initiated once the infection had already been established. The protection involving enhanced phagocytosis and then neutrophil mediated killing of infected cells was IgA isotype mediated, because treatment with an IgG version of 2E9 antibody was not effective in human IgG receptor CD64 transgenic mice. The Acr antigen specificity of IgA antibodies for protection in humans has been indicated by their elevated serum levels in latent tuberculosis unlike the lack of IgA antibodies against the virulence-associated MPT64 antigen. Our results represent the first evidence for potential translation of mucosal immunotherapy for the management of MDR-TB.